Technique of pelvic and paraaortic lymphadenectomy - Sláma, J; Kocián, R (Ceská gynekologie, 2016)
Overview of classification, anatomical conditions, methods and complications of pelvic and paraaortic lymph-node dissection. Review article. Department of Obstetrics and Gynecology, General Faculty Hospital and 1st Medical Faculty, Charles University, Prague. Lymphadenectomy is classified according to its extent into sentinel lymph-node biopsy, debulking, sampling and systematic procedure and according to approach into extraperitoneal or transperitoneal procedure. The most complex variant is systematic pelvic and paraaortic lymph-node dissection, which requires removal of fatty-lymphatic tissue from anatomically strictly defined areas. Procedure can be performed from laparotomy, laparoscopically or robotically. The main objective criterium of systematic procedure is the number of harvested nodes. The most common complications comprise bleeding and lymphocele formation. Pelvic and paraaortic lymphadenectomy represent basic component of surgical management in majority of gynecological cancers. The knowledge of extent, different techniques and ability to solve complications represents essential skill in gynecological oncology.